2002
DOI: 10.1117/12.483228
|View full text |Cite
|
Sign up to set email alerts
|

<title>Polymer optical fiber sensing</title>

Abstract: Development of single-mode polymer optical fibres, polymer materials and polymer fibre Bragg gratings has provided new opportunities for optical communication and other related applications. In this paper we report on recent progress and development of polymer optical fibres and devices that would have a significant impact on fibre sensing applications. We also present some of our preliminary experimental work on polymer optical fibre sensing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Peng et al [17] reported their experimental work on polymer optical fiber sensing. They used two POFBGs to separate the strain component and temperature component.…”
Section: Polymer Optical Fiber Strain Sensorsmentioning
confidence: 98%
“…Peng et al [17] reported their experimental work on polymer optical fiber sensing. They used two POFBGs to separate the strain component and temperature component.…”
Section: Polymer Optical Fiber Strain Sensorsmentioning
confidence: 98%
“…Single-mode POFs are presently obtainable commercially (e.g., Paradigm Optics Inc.) although their availability is still limited worldwide. Bragg gratings, which are commonly applied to single-mode silica fibres using ultra violet laser light to create the interference pattern to induce periodic changes in refractive index of the core, have also been demonstrated on doped plastic optical fibres and undoped bulk PMMA in recent years [17][18][19]. More recently, micro-structured POF have been introduced and these have received significant attention as a promising class of fibre for new sensor applications [20,21], achieving unique optical properties via a pattern of holes down the full length of the fibre.…”
Section: Introductionmentioning
confidence: 99%